Frontline Science: Late CD27 stimulation promotes IL-7Rα transcriptional re-expression and memory T cell qualities in effector CD8+ T cells. Issue 5 (14th June 2019) - Dong, Han; Buckner, Andrew; Prince, Jessica; Bullock, Timothy
Abstract: We previously demonstrated that CD27 co-stimulation during a primary CD8 + T-cell response was critical for the expression of IL-7Rα on acute effector CD8 + T cells, providing an essential element in the generation of CD8 + T-cell memory to infectious pathogens. IL-7 plays a critical role in the generation and maintenance of memory CD8 + T cells, and IL-7Rα has been regarded as a functional marker of long-lived memory precursor effector cells. While IL-7Rα is downregulated acutely upon TCR stimulation, the regulation of the emergence of IL-7Rα expressing cells around the peak of primary CD8 + responses is less clear. Re-expression could be a default outcome after withdrawal of TCR stimulation. Alternatively, specific stimuli could actively antagonize the downregulation or promote the recovery of IL-7Rα in Ag-activated CD8 + T cells. By utilizing agonistic mAb and transgenic models, here we show: (1) CD27 stimulation acts directly on CD8 + T cells to enhance IL-7Rα-expressing effectors; (2) CD27 stimulation neither alleviates the downregulation of IL-7Rα upon TCR signaling nor promotes the expansion/survival of IL-7Rα-expressing effectors, but facilitates IL-7Rα re-expression; (3) CD27 stimulation regulates Il7ra mRNA abundance but not protein distribution. Importantly, CD27 stimulation promotes not only IL-7Rα, but also the common γ chain of the receptor and the downstream signaling mediated by pSTAT5. Our results demonstrate a previously unappreciated role of CD27 stimulation as a positive regulator of IL-7Rα during CD8 T-cell responses, provide insights into the mechanistic basis by which CD27 stimulation influences CD8 + T-cell memory differentiation, and highlight the potential of targeting CD27-CD70 axis to enhance IL-7 signaling for antiviral/antitumor immunotherapy. Graphical Abstract: Late CD27 stimulation promotes CD8+ T cell memory differentiation by increasing transcription of IL7Rα and γc.